2016
DOI: 10.5433/1679-0359.2016v37n5supl2p3647
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological status of bovine tuberculosis in the State of Rio Grande do Sul, Brazil

Abstract: A study was conducted to determine the epidemiological status of bovine tuberculosis in the state of Rio Grande do Sul. The state was divided in seven regions, and in each of them, a pre-established number of farms was randomly sampled. In each farm, cows with age equal to or greater than 24 months were selected at random and submitted to the comparative cervical tuberculin test. The animals whose tests were inconclusive were retested with the same diagnostic procedure within a minimum interval of 60 days. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 25 publications
4
47
0
10
Order By: Relevance
“…Studies based on bovine tuberculosis, conducted in 12 Federative Units, which contain 75% of the Brazilian herd, showed herd prevalence estimates between 0.5% and 9.0% in Santa Catarina and São Paulo, respectively (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016;GALVIS et al, 2016;GUEDES et al, 2016;LIMA et al, 2016;NÉSPOLI et al, 2016;QUEIROZ et al, 2016;ROCHA et al, 2016;SILVA et al, 2016;VELOSO et al, 2016;VENDRAME et al, 2016). The same authors observed that the risk of bovine tuberculosis increased in larger dairy cattle herds on farms that use some degree of automation in the dairy production process.…”
Section: Resultsmentioning
confidence: 51%
“…Studies based on bovine tuberculosis, conducted in 12 Federative Units, which contain 75% of the Brazilian herd, showed herd prevalence estimates between 0.5% and 9.0% in Santa Catarina and São Paulo, respectively (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016;GALVIS et al, 2016;GUEDES et al, 2016;LIMA et al, 2016;NÉSPOLI et al, 2016;QUEIROZ et al, 2016;ROCHA et al, 2016;SILVA et al, 2016;VELOSO et al, 2016;VENDRAME et al, 2016). The same authors observed that the risk of bovine tuberculosis increased in larger dairy cattle herds on farms that use some degree of automation in the dairy production process.…”
Section: Resultsmentioning
confidence: 51%
“…Dairy herds were also found to have a higher risk of tuberculosis in New Zealand (PORPHYRE et al, 2008) and the United Kingdom (RAMÍREZ-VILLAESCUSA et al, 2010;KAROLEMEAS et al, 2011). In Brazil, this association was previously detected in the states of Bahia, Goiás, Mato Grosso, Minas Gerais, Paraná, Rio Grande do Sul, Santa Catarina, and São Paulo (BAHIENSE et al, 2016;ROCHA et al, 2016;NÉSPOLI et al, 2016;BARBIERI et al, 2016;SILVA et al, 2016;QUEIROZ et al, 2016;BAUMGARTEN et al, 2016;DIAS et al, 2016). Moreover, animals from dairy herds tend to be older than animals from beef herds, therefore having a higher likelihood of exposure to the infectious agent (HUMBLET et al, 2009).…”
Section: Discussionmentioning
confidence: 81%
“…This prevalence of infected herds is equal to those observed in the states of Bahia, Paraná, Rio Grande do Sul, Mato Grosso, Rondônia, Goiás, Pernambuco, and Distrito Federal. It exceeds the prevalence of infected herds in the State of Santa Catarina and is lower than those observed in São Paulo, Minas Gerais, and Espírito Santo (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016;GALVIS et al, 2016;LIMA et al, 2016;NÉSPOLI et al, 2016;QUEIROZ et al, 2016;RIBEIRO et al, 2016;ROCHA et al, 2016;SILVA et al, 2016;BAUMGARTEN et al, 2016;VENDRAME et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The extensive and systematic employment of milk pasteurization has significantly reduced the incidence of these diseases in the human population (SINHA, 1994). However, in countries such as Brazil, where these diseases are still currently widespread in herds (BRASIL, 2006a) and the consumption of dairy products prepared with raw milk persists (SOUSA, 2005; ROCHA et al, 2014), it is reasonable to accept the occurrence of human cases by this route of transmission, despite the lack of Brazilian epidemiological data corroborating this hypothesis.A recent study carried out in 13 Brazilian states, which hold 75% of the country cattle population, showed the prevalence of tuberculosis infected herds ranging from 0.36% in the Federal District to 9.0% in São Paulo (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016b;GALVIS et al, 2016;GUEDES et al, 2016;LIMA et al, 2016;NÉSPOLI et al, 2016;QUEIROZ et al, 2016;RIBEIRO et al, 2016;ROCHA et al, 2016;SILVA et al, 2016a;VELOSO et al, 2016;VENDRAME et al, 2016). In relation to bovine brucellosis, 18 Brazilian states were recently studied, comprising 85% of the country cattle population, and the prevalence ranged from 0.91% in Santa Catarina to 30.6% in Mato Grosso do Sul ALVES et al, 2009;ANZAI et al, 2016;BARDDAL et al, 2016;BAUMGARTEN et al, 2016; BORBA et al, 2013; CLEMENTINO et al., 2016;DIAS et al, 2009;DIAS et al, 2016a;INLAMEA et al, 2016;KLEIN-GUNNEWIEK et al, 2009;LEAL FILHO et al, 2016;OGATA et al, 2009;OLIVEIRA et al, 2016;ROCHA et al, 2009; SILVA et al, 2016b;SILVA et al, 2009).…”
mentioning
confidence: 99%